STUDI ANALISA PENANGANAN LONGSORAN PADA RUAS JALAN SAMARINDA – SEBULU STA 40 + 425 KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - GUNANTO, RUDI (KURVA S JURNAL MAHASISWA, 2018)
Planning for handling landslides on Samainda - Sebulu Sta. 40 + 425 Kutai Kartanegara Regenc,, Samarinda city, with retaining wall method. The Samarinda - Sebulu road is a road called inter-city road in the province, the area around this road has a bumpy topography in terms of hilly and valleys, because of this there are many landslides in this area. Overcoming landslides on sta. 40 + 425 is planned to construct Cantiliver type retaining walls, planning the construction through stages such as collecting actual field data (topography and soil investigation data) to analysis of shape, dimensions and stability of construction. This construction will later overcome landslides. The analysis method used to handle avalanches is the calculation method of Rankine and Coloumb From the calculation results, the Rankine and Coloumb methods can be concludedn that the planned dimensional stability of the retaining wall to hold the soil is safe against both rolling and shear forces, so that it is not necessary to plan pile foundations to resist working rolling and shear forces.